THE CAPABILITY ENHANCEMENT TRAINING READING COMPREHENSION: First and Second Grade in Enrekang Regency through Pictorial Story Media and SQ3R Method - Musdalifah Ifah Rahman; Mustakim Mustakim; Elihami Elihami (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2020)
Community service activities (PKM) carried out by the implementing team provided a brief description of the procedures for implemented and used pictorial story media and the SQ3R method in the learning process and the process of enhanced students' understanding ability in reading sources or reading material they had. The PKM activity was carried out in Enrekang Regency south Sulawesi district. The school chosen as the object of this PKM activity that was SMA Negeri 2 Enrekang. Participants who were the targets of this PKM activity were first and second grade students of SMA Negeri 2 Enrekang. The organizing committee for community service activity (PKM) chosen first and second grade students of SMA Negeri 2 Enrekang because most of their reading learning materials were closely related to understood process fill in the reading material in detail. The main objectives or benefits of the community service activity (PKM) were: first, the community service activities (PKM) provided knowledge about pictorial stories media and SQ3R method. And the second was community service activities (PKM) that provided tips, strategies, and new methods for English teachers in locations that were the object of community service activities (PKM) so that they could help them increased their students' reading comprehension. Keywords: Pictorial Story Media, and SQ3R Method.